Program Pemberdayaan Masyarakat “Saudagar Halal Madiun” pada UMKM di Kabupaten Madiun: Community Empowerment Program "Madiun Halal Merchants" for MSMEs in Madiun Regency - Gama, Zulfaidah Penata; Setyawan, Erlangga; Kusumastuti, Dinda Amelia; Alfandia, Nurlita Sukma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Lack of understanding of financial records can cause owners to have poor asset management skills. Apart from that, taxes for MSMEs are another problem for business actors. The existence of demands from the government regarding halal certification also means that business actors who sell food and drinks are required to obtain halal certification. The aim of this activity is that business actors can compile simple records of the business carried out, know their tax obligations, and be able to calculate the amount of tax paid themselves. Participants are expected to be able to have halal certification for their businesses, especially businesses with food and beverage products. Community empowerment was carried out in Madiun Regency on 26-27 July 2023. Participatory Action Research (PAR) is used in this community service. Community empowerment is carried out through skills training, counseling, and development of micro, small, and medium enterprises (MSMEs). In this method, participants will make and learn from changes made in the training process. Simple bookkeeping training, MSME taxation, and submission of halal certification are the three sessions that make up the activities. In conclusion, MSME owners still need financial records written on paper, and most still need to try to record them. Most participants have small gross receipts or businesses with gross receipts of less than Five hundred million per year, so companies are not subject to MSME tax. Participants' enthusiasm grew when they helped apply for halal certification.